Bis(N-isobutyl-N-propyldithiocarbamato-kappa S-2,S `)zinc(II) - Awang, N.; Baba, I.; Yamin, B.M.; Ng, S.W. (International Union of Crystallography, 2010)
In the title compound, [Zn(C8H16NS2)(2)], the Zn-II atom is chelated by two S,S'-bidentate dithiocarbamate ions in a very distorted tetrahedral geometry. The alkyl chains of the ligands are equally disordered over two sets of sites.